Plasticization and cocrystallization in LLDPE/wax blends. Issue 15 (16th March 2016) - Gumede, Thandi P.; Luyt, Adriaan S.; Pérez‐Camargo, Ricardo A.; Iturrospe, Amaia; Arbe, Arantxa; Zubitur, Manuela; Mugica, Agurtzane; Müller, Alejandro J.
ABSTRACT: The structure and thermal properties of linear low‐density polyethylene (LLDPE)/medium soft paraffin wax blends, prepared by melt mixing, were investigated by differential scanning calorimetry (DSC) and small‐ and wide‐angle X‐ray scattering (SAXS and WAXS). The blends form a single phase in the melt as determined by SAXS. Upon cooling from the melt, two crystalline phases develop for blends with more than 10 wt % wax characterized by widely different melting points. The wax acts as an effective plasticizer for LLDPE, decreasing both its crystallization and melting temperature. The higher melting point crystalline phase is formed by less branched LLDPE fractions. On the other hand, the lower melting point crystalline phase is a wax‐rich phase constituted by cocrystals of extended chain wax and short linear sequences of highly branched LLDPE chains. The presence of cocrystals was evidenced by standard DSC results, successive self‐nucleation and annealing (SSA) thermal fractionation and by the detection of a new SAXS signal attributed to the lamellar long period of the cocrystals. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2016, 54, 1469–1482 Abstract : Wax acts as an effective plasticizer for linear low‐density polyethylene (LLDPE), decreasing both its crystallization and melting temperature. For 70/30 LLDPE/wax blends, two phases are formed: a high temperature melting phase that is composed of LLDPE crystals with a mixed amorphous phase containing wax and LLDPE chains, and a low temperature melting phase containing LLDPE‐wax cocrystals and a mixed amorphous phase.